The Influence of Work Motivation And Work Discipline On Employee Performance At PT. The Goodwood Interior Design Cengkareng, West Jakarta - Marom, Muhammad Aufal; Astuti, Endang Puji (Pascasarjana STIE Miftahul Huda, 2025)
This research aims to determine the variables of the influence of work motivation and work discipline on employee performance at PT. The Goodwood Interior Design Cengkareng, West Jakarta. The method used in this research is an associative quantitative research method where the data obtained is in the form of a questionnaire which is processed using the SPSS 2.6 application. Data analysis used includes: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Autocorrelation, Simple Linear Regression, Multiple Linear Regression, t Test (Partial), F Test (Simultaneous), Correlation Coefficient (R) and Determination Coefficient (R2). The results of the research partially show that motivation has a significant effect on employee performance as seen from the t test, the value obtained is tcount > ttable (5.322 > 1.99167) and is significant 0.000 < 0.05. Then, the work discipline variable has a significant effect on employee performance, seen from the t test, the value obtained is tcount > ttable (4.414 > 1.99167) and is significant 0.000 < 0.05. Then simultaneously the motivation variable and the work discipline variable have a significant effect on employee performance as evidenced by the Fcount value of 63.502 and a significance value of 0, while the Ftable value is at a significance level of 0.05 with df 1 (number of variables -1) 3-1 = 2, and df 2 (nk-1) or = 78-2-1 = 75, the F table value is 3.12. So it can be concluded that Fcount > Ftable (63.502 > 3.12) and significance < 0.05 (0 < 0.05), then Ha is accepted, so it can be concluded that Work Motivation and Work Discipline together influence employee performance.